An Automated Way of Baking Process for Moisture Sensitive Components - A. Ramamoorthy; M. Jagadeeshraja; L. Manivannan; K. Raja (Institute of Advanced Engineering and Science, 2016)
The objective of my project is to the new technology termed as “baking process” to remove the moisture content available in the particular electronics devices which is used in Rea time industrial application. In Industries there are certain policies are maintained for semiconductor devices, which referred as “Shelf life” of the material. Once it crossed its lifetime, some process need to done to extend this. Depends on the moisture sensitive characteristics baking is employed mainly to shelf life extension. The Baking is the process of removing of moisture content from particular semiconductor device in order to effective usage in the production line. In my propose method the moisture content is measured by corresponding moisture sensor. If it is normal level the processor goes to the normal state, If it is reaches the abnormal level (presence of moisture) the processor baked the product. Temperature and humidity sensors are effectively monitor and provide the signal to the processor. The UTLP kit provide the information about the status of the product.